Climate risk perception, management, and adaptation in the Nordic mining sector - Klein, Johannes; Käyhkö, Janina; Räsänen, Aleksi; Groundstroem, Fanny; Eilu, Pasi (Elsevier BV, 2022)
Climate change can affect the mining sector in various ways. Physical impacts can be a threat to mines and personnel, transport infrastructure and supply chains, while the low-carbon transition may entail transition risks stemming from e.g., the need to respond to mitigation and adaptation policies, as well as opportunities in the form of increased metal and mineral demand. However, there is little knowledge of how mining companies perceive, manage, and respond to risks related to climate change. To address this knowledge gap, we examined annual and sustainability reports from 2019 for active metal mines in Finland, Sweden, and Norway. Through a structuring qualitative content analysis, we analysed the mining companies’ self-reported experience of and expectations for climate change impacts and risks, as well as adaptation and management activities taken or planned. Our findings indicate that physical impacts of climate change are not perceived as a major risk. In contrast, mitigation activities and reactions to climate policies play an important role, at least for some of the companies. Hence, the mining sector would benefit from more stringent risk reporting regulations and distinctive guidelines, as well as more research on the direct and indirect climate change impacts.
Keywords: Climate change; Mining; Adaptation; Transition risks; Extractive industries